Analysis to Increase the Recovery and Quality of Zinc Concentrate in Polymetallic Ore Flotation in the Yarusyacán District, Cerro de Pasco - Barrientos Ríos, José (2025)
Ore from the Yarusyacán District was analyzed in this research study, revealing the presence of sphalerite type 2, with a particle size ranging from 35 to 150 microns. Other species found included quartz, pyrite, pyrrhotite, calcium and potassium silicates, calcium carbonates, galena, chalcopyrite, and iron hydroxides. Based on the mineralogical characterization, laboratory tests were conducted that showed that dosing a secondary collector known as cuprocyanide can control the recovery and quality of the zinc concentrates in the third cleaning feed.  Results showed that a 35 g/t dosage of cuprocyanide recovered 73.80% of zinc, whereas a 50 g/t dosage recovered only 52.94%. This demonstrated that both zinc grade and recovery increase when cuprocyanide is dosed in greater quantities; however, the excess of this reagent tends to decrease said values.